Photosynthetic Functioning As A Selection Criteria For Maximum Yield Potential In Some Wheat Genotypes Under Late Planting Heat Stress Conditions. (International Journal of Scientific Research and Management (IJSRM), 2017)
Heat stress had profound effect on the photosynthetic efficiency. This study demonstrated a large degree of genotypicvariability in net photosynthesis, stomatal conductance and rate of transpiration among 40 wheat genotypes afteranthesis under late planting high temperature field conditions when compared with the timely sown. CTD measured inthe flag leaf was significantly correlated with grain yield when measured after anthesis, with correlation coefficients of0.389* (P <0.01) and 0.602** (P><0.01) for timely and late sown respectively. In certain genotypes cooler canopy andhigh stomatal conductance after anthesis would be assumed as the basic morpho-physiological criteria for higher grainyield under heat stressed conditions. Ci measured in the flag leaf was significantly correlated with grain yield whenmeasured at anthesis only in late sown conditions, with correlation coefficients of 0.320* (P><0.01). There was foundthe overall decrease in the P(n) with the delay in sowing. Tr measured in the flag leaf was significantly correlated withgrain when measured after anthesis, with correlation coefficients of 0.718*** (P><0.0001) and 0.502** (P><0.01) fortimely and late sown respectively. This study showed that the photosynthetic rate of wheat genotypes grown under lateplanting field conditions varies greatly and is significantly associated with grain yield. The associations found betweennet photosynthesis, stomatal conductance, grain yield, contribute significantly to our understanding of the mechanismsdetermining potential productivity in superior germplasm under hot conditions.The studied correlation suggest thatPn, and Tr were found to be effective traits defining wheat genotypes adapted to production systems prone to hightemperature stress during the anthesis period.>